THE PRACTICE OF ENGLISH LANGUAGE TEACHING AND LEARNING IN SEKOLAH BUIN BATU PT. NEWMONT NUSA TENGGARA, WEST SUMBAWA, NTB PROVINCE - B1, AQLI,; N, PADMADEWI,; W, SUARNAJAYA, (Universitas Pendidikan Ganesha, 2013)
Abstract This study aimed at (1) describing how English teachers at Middle Years of Sekolah Buin Batu (SBB) develop curriculum; (2) describing how English teachers at Middle Years of SBB determine learning resources;(3) describing how English teachers at Middle Years of SBB deliver learning activities, and; (4) describing how English teachers at Middle Years assess students? learning progress. The subjects of the study were the English teachers and students at Middle Years of SBB in the academic year 2011/2012. The data were collected using some methods of data collection namely interview, observation, and documentation. Interview and documentation were used to collect data of curriculum and learning resources while interview, observation, and documentation were used to collect data of learning activities and assessment. The result of the study indicated that (1) English teachers at Middle Years of SBB develop curriculum. The teachers develop curriculum based on curriculum development procedure which covers the stages in team development and common understanding of curriculum development at SBB including inventory making, need analysis, drafting, verification, validation, finishing, approval, filing and archiving; (2) English teachers at Middle Years of SBB use various types of resources and identify teaching learning resources based on teachers? planning to achieve teaching learning objectives, propose to school leaders, request the resources through administration staff, purchase the resources after the Purchase Order (PO) is approved by Finance and Admin Manager; (3) English teachers at Middle years of SBB teach English based on Year level and use various types of methods recognizing every individual abilities and learning styles (4) English teachers at Middle Years of SBB employ various kinds of assessment techniques based on the school assessment policy and the learning objectives Keywords: ELT, Curriculum Development, Learning Resources, Learning Activities, Learning Assessment